(untitled) (Canadian Journal of Native Studies, 2026)
Abstract Turning Stones is a family-centered domestic violence intervention program in British Columbia, Canada. This culturally sensitive program serves Indigenous men, women, and youth/children who suffer as a result of abuse in one or more intimate relationships. The study describes the Turning Stones program and provides a preliminary examination of program impacts based on nine men and nine women enrolled in the program. The program shows promising results with respect to decreasing abusive behaviours, with participants reporting declines in both physical and psychological abuse following program completion. Male participants also demonstrated gains in knowledge and skills concerning anger reduction. The limitations of the study and future research are discussed.